An Open Source Custom K-means Generator for AWS Cloud FPGA Accelerators - Bragança, Lucas; Canesche, Michael; Penha, Jeronimo; Carvalho, Westerley; Comarela, Giovanni; Nacif, José Augusto M.; Ferreira, Ricardo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2021: Anais do XI Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2021)
Nowadays, FPGAs play an essential role in domain-specific hardware accelerators due to their power efficiency and flexibility. Nevertheless, FPGA programming and deploying are still a challenge. We present an accelerator generator targeting Amazon Web Services (AWS) Cloud FPGAs. We validate our generator with the K-means clustering algorithm as a case study. The main contribution of this work is to present an opensource full-stack generator using AWS EC2 F1 cloud FPGAs. Our framework is parameterizable and generates Verilog code for the entire design, including DDR memory and FPGA communication. Furthermore, we use a modular design approach, allowing extensions to address other applications. Compared to the Intel/Altera Harpv2 cloud FPGA, our AWS accelerator is on average twice faster for the K-means case study.